2007
DOI: 10.1007/s10546-007-9161-1
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Balance Experiment EBEX-2000. Part I: overview and energy balance

Abstract: An overview of the Energy Balance Experiment (EBEX-2000) is given. This experiment studied the ability of state-of-the-art measurements to close the surface energy balance over a surface (a vegetative canopy with large evapotranspiration) where closure has been difficult to obtain. A flood-irrigated cotton field over uniform terrain was used, though aerial imagery and direct flux measurements showed that the surface still was inhomogeneous. All major terms of the surface energy balance were measured at nine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
272
2
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 336 publications
(308 citation statements)
references
References 49 publications
(46 reference statements)
17
272
2
8
Order By: Relevance
“…Note that the accuracy of J C relies on the quality of GPP data. Some of the energy fixed by photosynthesis is steadily released by respiration and is already accounted for in sensible heat storage change J H and heat storage change of biomass J veg (Blanken et al 1997;Oncley et al 2007). J C adds energy to the storage and should be therefore positive during day and is zero during periods without photosynthesis, i.e.…”
Section: Biochemical Heat Storage Change J Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the accuracy of J C relies on the quality of GPP data. Some of the energy fixed by photosynthesis is steadily released by respiration and is already accounted for in sensible heat storage change J H and heat storage change of biomass J veg (Blanken et al 1997;Oncley et al 2007). J C adds energy to the storage and should be therefore positive during day and is zero during periods without photosynthesis, i.e.…”
Section: Biochemical Heat Storage Change J Cmentioning
confidence: 99%
“…There are numerous studies reporting a lack of energy closure (e.g. Aubinet et al 2000;Barr et al 1994Barr et al , 2006Bernhofer 1992;Bernhofer and Vogt 1999;Blanford et al 1991;Blanken et al 1998;Finch and Harding 1998;Jarvis et al 1997;Kabat et al 1997;Laubach 1996;Malhi et al 2002;Oncley et al 2007;Twine et al 2000;Wilson et al 2002;Wilson and Baldocchi 2000). Wilson et al (2002) found an imbalance in the order of 20% for a number of FLUXNET sites.…”
Section: Introductionmentioning
confidence: 99%
“…In general, EBC ranges between 70 and 90 % as observed over different types of surface ranging from bare soil to a forest (Oncley et al, 2007;Wilson et al, 2002;Twine et al, 2000). Low EBCs (60-80 %) were mainly observed at various agricultural sites and bare soil, whereas over forest they were typically higher (80-90 %) (Charuchittipan et al, 2014;Wilson et al, 2002;Foken, 2008a;Panin and Bernhofer, 2008;Stoy et al, 2013).…”
Section: K Imukova Et Al: Energy Balance Closure On a Winter Wheat mentioning
confidence: 99%
“…Minor flux terms such as energy storage in the canopy or energy conversion by photosynthesis are generally neglected (see e.g., Leuning et al, 2012). However, several studies, where minor energy fluxes were carefully investigated as potential sources for the imbalance, show that considering these minor terms is relevant (Lamaud et al, 2001;Meyers and Hollinger, 2004;Oncley et al, 2007) and could even in some cases help to achieve a nearly perfect EBC (Jacobs et al, 2008). Usually the sum of the two turbulent fluxes measured with the EC method is systematically lower than the so-called available energy: the difference between net radiation (R n )…”
Section: Introductionmentioning
confidence: 99%
“…The software package TK3 (Mauder and Foken, 2011) post-processed high frequency (20 Hz) raw data to calculate 30-min aggregated fluxes of NEE and generate the observed database (Database-observation). This flux calculating and correcting strategy is well documented, intercompared by the international micrometeorology community (Mauder et al, 2008), and successfully applied during known major field experiments such as EBEX-2000 Oncley et al, 2007), LITFASS-2003, and COPS-2007 (Eigenmann et al, 2011). Automatic weather stations (AWS, WS-GP1, Delta-T Devices Ltd., UK) were used at both sites for the measurement of meteorological variables (5-min values), including air temperature, humidity, wind speed and direction, precipitation, and global radiation.…”
Section: Data Collectionmentioning
confidence: 99%